2017
DOI: 10.18632/oncotarget.17465
|View full text |Cite
|
Sign up to set email alerts
|

αMSH inhibits adipose inflammation via reducing FoxOs transcription and blocking Akt/JNK pathway in mice

Abstract: Alpha melanocyte stimulating hormone (αMSH) abates inflammation in multiple tissues, while Forkhead box proteins O (FoxOs) stimulate inflammatory cascade. However, the relationship between αMSH and FoxOs in adipose inflammation remains unclear. In this study, we used LPS-induced inflammation model, attempted to interpret the function of αMSH in inflammation and the interactions with FoxOs. Results indicated that upon inflammatory situation, the secretion of αMSH and the expression of its receptor MC5R were gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Previously, the BMP/Smad and Akt/MAPK/NF-κB pathways were found to contribute to rh-SHH-induced osteoblastic or cementoblastic differentiation [23], and a stepwise pathway involving Akt/JNK or Akt-MAPK/ERK was demonstrated to regulate cell inflammation, an undifferentiated state and viability [25,59]. These findings are consistent with our data that JNK activation induced by M2 Mφs was inhibited by the addition of Akt inhibitor (Fig.…”
Section: Stem Cellssupporting
confidence: 93%
See 2 more Smart Citations
“…Previously, the BMP/Smad and Akt/MAPK/NF-κB pathways were found to contribute to rh-SHH-induced osteoblastic or cementoblastic differentiation [23], and a stepwise pathway involving Akt/JNK or Akt-MAPK/ERK was demonstrated to regulate cell inflammation, an undifferentiated state and viability [25,59]. These findings are consistent with our data that JNK activation induced by M2 Mφs was inhibited by the addition of Akt inhibitor (Fig.…”
Section: Stem Cellssupporting
confidence: 93%
“…Given that the Wnt/β-catenin, Akt, TGF-β/Smad, BMP/Smad, and MAPK pathways have been demonstrated to regulate the osteogenesis/cementogenesis process [20][21][22][23][24][25][26][27][28], key genes involved in the above pathways were selected to screen the potential pathways that regulate M2 Mφ-enhanced cementoblastic differentiation. When the expression of the selected genes in CM-M2-treated PDLSCs (M2 group) and untreated PDLSCs (Control group) was analyzed using qRT-PCR, the pathway-related genes that were differentially expressed between the two groups were plotted in a heatmap (Fig.…”
Section: Potential Pathways Involved In M2 Mφ-enhanced Cementoblasticmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the exosomal release from these cells and the consequent exosomes-induced node and tube formation in the HUVEC were significantly reduced by ARPE-19 treatment with PG-901, a melanocortin receptor MCR 5 agonist. The MCR 5 receptor plays a role in glucose metabolismand inflammation-based pathologies [29,30], and is expressed in retinal pigment epithelial cells [4]. Human studies showed that single-nucleotide polymorphism in the MCR 5 was associated with type 2 diabetes in obese subjects, while experimental in vivo and ex vivo studies demonstated that a glucose uptake in skeletal muscles driven by α-MSH is markedly reduced in MCR 5 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-luciferase reporter assay procedure was performed as described in Liu et al (27). The fragment of the 3′-untranslated region (UTR) of Wnt3a for miR-103 and miR-107 was synthesized and cloned into the region of the PGL3 vector.…”
Section: Reporter Constructs and Dual-luciferase Reporter Assaysmentioning
confidence: 99%